STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI DAN KINERJA GURU - Musnani, Musnani; Mahmud, Muchammad Eka; Idris, Husni (STKIP PGRI Situbondo, 2024)
This research is that teachers have a noble duty as educators. However, some conditions can threaten the implementation of the teacher's duties and role, so teacher motivation and performance must always be improved by the school principal with appropriate and good strategies. There are three research objectives, namely: to analyze the principal's strategy in increasing teacher motivation, to analyze the principal's strategy in improving teacher performance, and to analyze the supporting and inhibiting factors of the principal in increasing teacher motivation and performance in SD Negeri 001 and SD Negeri 011 North Sangatta. This type of research is descriptive qualitative, research at SD Negeri 001 and SD Negeri 011 Sangatta Utara. Data collection techniques use observation, interviews, and documentation, as informants are the school principal and teachers. Data was analyzed using the Miles Huberman model with data collection, condensation, data presentation, and conclusion. The results of this research show (1). The principal's strategy in increasing teacher motivation is: The strategy is to use efforts to remind teachers that teaching is a noble job, teachers must not complain, teachers must establish good relationships with all teachers, and create a pleasant environment and conditions. Another strategy is to motivate the form of recognition and appreciation, focus on work-life balance, and teachers must maintain a positive spirit. as well as knowing the environment and character, and maximizing all activities carried out by the teacher. (2). The principal's strategy for improving teacher performance is that the principal's strategy for improving teacher performance focuses on work-life balance, not be afraid of innovation, being very active in motivating teachers, adequate allowances, always providing opportunities for self-development, teachers developing themselves, improving teacher professionalism, Forming collaborative teams through learning communities, Involving all parties. That the principal communicates well and that cooperation in every activity is carried out well. Even if there are problems, they can be resolved with good communication.